PENGARUH PROGRAM MAKANAN BERGIZI GRATIS (MBG) TERHADAP KONSENTRASI BELAJAR DAN KEDISIPLIAN BELAJAR PESERTA DIDIK DI SD NEGERI WOLIBANG - Yuliana M. Bail; Antonius A. Saetban; Petrus Mau Tellu Dony (CV. Adiba Aisha Amira, 2026)
This study was motivated by the low level of students' learning concentration and learning discipline at SD Negeri Wolibang. Some students came to school hungry, making it difficult for them to concentrate during lessons. They were easily drowsy, less active in classroom learning activities, and had not fully complied with school rules and regulations. To address these problems, the government implemented the Free Nutritious Meal Program (MBG) as an effort to improve students' nutritional status and learning readiness. This study aimed to determine the effect of the Free Nutritious Meal Program (MBG) on students' learning concentration and learning discipline at SD Negeri Wolibang. This study employed a quantitative research method using an ex post facto research design. The population consisted of all 70 students of SD Negeri Wolibang. Data were collected through questionnaires and observations. The data were analyzed using descriptive statistics and presented in the form of tables, percentages, and charts to describe the effect of the Free Nutritious Meal Program (MBG) on students' learning concentration and learning discipline.The results of the study indicate that the Free Nutritious Meal Program (MBG) has a positive effect on students' learning concentration and discipline. The students became more focused during classroom learning, more actively participated in learning activities, and demonstrated greater discipline in complying with school rules and regulations. Based on these findings, it can be concluded that the Free Nutritious Meal Program (MBG) has a positive effect on improving students' learning concentration and learning discipline at SD Negeri Wolibang.